A cross-sectional analysis of coffee intake and hypertension prevalence: results from the NHANES 2005–2020 - Li, Hua; Chen, Wei; Zeng, Zao; Ding, Ning; Luo, Ju; Li, Keng (Frontiers in Nutrition, 2025)
ObjectiveTo investigate the association between coffee consumption and hypertension risk.MethodsUsing data from the 2005–2020 National Health and Nutrition Examination Survey (NHANES) on 41,685 adults, multivariable logistic regression models examined the relationship between categorical coffee intake (none, >0 to < 1, ≥1 to < 2, ≥2 to < 3, ≥3 to < 4, and ≥4 cups/day) and hypertension, with stratified and curve-fitting analyses.ResultsCompared to non-consumers, moderate daily intake of 1–3 cups was significantly associated with lower hypertension odds (OR 0.829–0.869, p < 0.05), more prominently in those < 60 years (OR 0.957, 95% CI 0.940–0.975). Curve fitting revealed a U-shaped association between coffee consumption and hypertension risk.ConclusionWhile a moderate coffee intake (1–3 cups/day) was associated with a lower prevalence of hypertension, especially among adults under 60 years, this cross-sectional study cannot establish causality. Further prospective studies are needed to confirm these findings.